Efficacy of vitamin D3 supplementation on cancer mortality in the general population and the prognosis of patients with cancer: protocol of a systematic review and individual patient data meta-analysis of randomised controlled trials - Schöttker, Ben; Kuznia, Sabine; Brenner, Hermann (BMJ open, 2021)
Introduction Vitamin D insufficiency is much more common among patients with cancer than the general population. Previous meta-analyses of controlled trials showed an approximately 15% reduction of cancer mortality by vitamin D supplementation compared with placebo or no treatment in the general population.On top of updating the latest systematic review on vitamin D supplementation and cancer mortality in the general population, we aim to conduct the first meta-analyses of trials on vitamin D3 supplementation and cancer-specific and overall survival of patients with cancer. Besides, we will conduct for the first time subgroup analyses based on individual patient data collected from randomised controlled trials. - Methods and analysis A systematic review and individual patient data meta-analysis will be performed on randomised placebo-controlled trials with a vitamin D3 intervention. All databases are searched from inception without time restriction. The addressed outcomes are cancer mortality in the general population as well as cancer-specific and overall survival of patients with cancer. The quality appraisal of the studies will be evaluated by the Cochrane risk-of-bias tool for randomised trials. Trial results will be reanalysed using adjusted and unadjusted Cox proportional hazard regression models and meta-analyses are planned. Cochran’s Q-Test and the I2 index will be used to statistically assess the level of heterogeneity, while sensitivity and subgroup analyses serve to identify potential causes of heterogeneity. Subgroup analyses will be conducted for vitamin D3 dosing, follow-up time, age, sex, obesity, vitamin D deficiency/insufficiency, history of cancer and compliance. Publication bias will be assessed by funnel plots and Egger’s test. - Ethics and dissemination Ethical approval is not required since no human beings are involved in this systematic review. Results will be published in a peer-reviewed journal with open access. They will be presented at conferences and sent to patient advocacy groups and German oncological rehabilitation centres. - PROSPERO registration number CRD42020185566
Im Titel ist die Zahl 3 tiefgestellt
Gesehen am 01.06.2022